CÂT ȘI CUM PUBLICĂ CERCETĂTORII DIN REPUBLICA MOLDOVA? - CUCIUREANU, Dr.,cercetător științific superior, Institutul de Dezvoltare a Societății Informaționale al AȘM, Gheorghe (BIBLIOPOLIS, 2020)
The analysis of trends highlighted in UNESCO Science Report: towards 2030 offered the possibility to evaluate the scientific productivity of the Moldavians in 2005-2014. The report permitted to identify the causes of small values of indicators related to scientific publications in the Republic of Moldova. The author analyses the distribution of the financial resources, the scientific productivity, the level of international recognition and the rewards of excellent results. The author’s conclusion resumed to the fact that a few number of researcher are part of international scientific circulation and only 15% of national project coordinators have published ISI-Thomson indexed articles – the majority up to an article annual. The author also addresses the problem of national and academic awards.